Synthesis of Fe₃O₄ using the Co-precipitation Method with Temperature and Time Treatment as Methylene Blue Adsorbent - Kuntjahjono, Mayang Fauziah Putri; Lestari, Aura Puja; Nurhalimah, Siti; Sarweswara, Wikrama; Purba, Farelino Oktavianus; Kaunang, Andrew Miracle; Sasongko, Nugroho Adi; Rahmat Basuki (Indonesian Scholar Society, 2025)
Magnetite nanoparticles (Fe₃O₄) possess unique magnetic properties and are widely applied in various fields such as biomedical technology, environmental remediation, and material separation. This study reports the synthesis of Fe₃O₄ using the co-precipitation method under varying conditions of temperature, reaction time, and atmospheric exposure (open vs. closed system). Ferric and ferrous salts were reacted with ammonium hydroxide under controlled heating at 70°C and 80°C for 60 minutes. The synthesized materials were evaluated through visual color inspection, qualitative magnetic response, yield efficiency, and magnetic load-bearing capacity. The results showed that a closed system at 80°C produced the most optimal Fe₃O₄, indicated by a deep black color, strong magnetic attraction (149.86 mN), and a yield of 92.5%. Comparatively, open systems led to partial oxidation of Fe², resulting in less magnetic phases like maghemite or hematite. The findings confirm that controlling synthesis parameters, especially atmospheric exposure and temperature, significantly influences the purity, particle uniformity, and magnetic strength of Fe₃O₄ nanoparticles, highlighting the importance of optimized synthesis for practical applications.